JOGED DANCE IN YOUTUBE - Suartaya, Kadek; Suastika, I Made; Dibia, I Wayan; Agung, Anak Agung Gde Putra (E-Journal of Cultural Studies, 2016)
In Indonesia Joged Bumbung is a dance which was created in Bali; it is known as tari pergaulan, namely, a social dance which is performed to make friends; however, it has   innovated so freely that it becomes a dance with pornographic movements  presented vulgarly.   The recording of such a dance can be easily watched in YouTube; it can also be easily watched in shared video web sites, through which the users can download, watch and share different video clips free of charge. The problems of the present study are (1) what is the negative impact of the pornographic joged dance on the aesthetic values of Joged Bumbung; (2) how negatively people view the dancers and group of such a pornographic joged dance; (3) how negatively people view the Balinese cultural art resulting from the fact that such a pornographic joged dance has been uploaded in YouTube? The main objective of the present study is to identify the negative impact of the pornographic joged dance in YouTube. The data were collected through observation, interview, and library research. The collected data were then analyzed descriptively and qualitatively using the phonological theory; and the qualitative method is used. It can be concluded that the pornographic joged is still watched in different parts of the island; it is watched every night. The government, art observers, and the society’s leaders are anxious about the negative impact of such a joged dance on those who are involved in its performance. Therefore, the Bali government has persuaded the dancers and groups that are involved in the performance of such a joged dance to return to the ethical choreography of the performing art of Joged Bumbung. The government has directly met them for this purpose; however, what has been done has not been successful yet. There were three negative impacts of such a joged dance presented in YouTube. They are (1) the art value of the Joged Bumbung dance has become degraded; (2) the dancers have been immorally justified; and (3) the Balinese art and culture have been distorted.